Women's age at first marriage and marital instability: Evidence from the 2006-2008 national survey of family growth - Evelyn L. Lehrer; Yu Chen (Institute for the Study of Labor (IZA), 2011)
One of the most salient demographic trends in the U.S. landscape in recent decades has been the pronounced increase in age at first marriage. This paper examines the implications of women's delayed entry to marriage for marital stability using data from the 2006-2008 National Survey of Family Growth. The main finding is that the association between age at marriage and marital instability without holding constant the couple's characteristics at marriage is negative up to the late twenties, with the curve leveling off thereafter. Women who marry in the late twenties and thirties generally enter unconventional matches (e.g., the husband is more likely to have been married before, and to be younger than the wife by three years or more), suggestive of a poor match emerging as the biological clock begins to tick. However, the flattening out of the curve beyond the late twenties suggests that the stabilizing influence associated with greater maturity at older ages is strong enough to cancel out the poor match effect.
urn:nbn:de:101:1-201109297531
Keywords: J12; 330; divorce; marriage dissolution; marital instability; marriage; Ehe; Frauen; Altersgruppe; Dauer; Scheidung; USA